2021
DOI: 10.5455/msm.2021.33.250-256
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Language Skills of Autistic Spectrum Disorders in Children and Their Parents' Emotions

Abstract: Background: Autism spectrum disorder (ASD) is a developmental disability, which is a biologically based neurodevelopmental disorder that affects a child’s social interaction and communication skills. Core deficits are identified in two domains: social communication/interaction and restrictive, repetitive patterns of behavior. Children and youth with ASD have service needs in behavioral, educational, health, leisure, family support, and other areas. Autism is a set of heterogeneous neurodevelopment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
3
0
7
Order By: Relevance
“…De la misma manera, los procesos cognitivos y de funcionamiento ejecutivo se ven afectados por las limitaciones en el lenguaje (Rossi et al, 2013). Varios estudios demuestran que, al no presentar un lenguaje expresivo adecuado para su edad cronológica, aparecerán alteraciones en el pensamiento lógico, la memorización y problemas de conducta dificultando, así el correcto desarrollo de las funciones cerebrales durante las primeras etapas del crecimiento madurativo (McIntosh et al, 2016;Ibrahimagić et al, 2022). En la Tabla 1, se presenta un resumen de las principales alteraciones cognitivo-lingüísticas de las personas con TEA y epilepsia en la etapa infantil:…”
Section: Características De Las Alteraciones Lingüísticas Y Otras Fun...unclassified
“…De la misma manera, los procesos cognitivos y de funcionamiento ejecutivo se ven afectados por las limitaciones en el lenguaje (Rossi et al, 2013). Varios estudios demuestran que, al no presentar un lenguaje expresivo adecuado para su edad cronológica, aparecerán alteraciones en el pensamiento lógico, la memorización y problemas de conducta dificultando, así el correcto desarrollo de las funciones cerebrales durante las primeras etapas del crecimiento madurativo (McIntosh et al, 2016;Ibrahimagić et al, 2022). En la Tabla 1, se presenta un resumen de las principales alteraciones cognitivo-lingüísticas de las personas con TEA y epilepsia en la etapa infantil:…”
Section: Características De Las Alteraciones Lingüísticas Y Otras Fun...unclassified
“…Among the features of expressive speech in autism spectrum disorders, it is customary to distinguish echolalia, verbal rituals, the use of neologisms and idiosyncratic speech, the misuse of personal pronouns and verb endings (Akhmetzyanova, Artemieva & Gryaznova, 2021). These children exhibit very unusual language and communication patterns, such as stereotyped speech, and odd and ritualistic behaviors (Ibrahimagic et al, 2021).…”
Section: Employing Psycholinguistic Activities To Improve Expressive ...mentioning
confidence: 99%
“…As a result, these children miss the opportunities to participate in exciting experiences with others. They manifest instances of immaturity in communication skills, leading to emotion management defects (15,16). In this regard, some studies have reported that autistic individuals have trouble identifying emotions (10,17,18).…”
Section: Introductionmentioning
confidence: 99%